Edgar Allan Poe et les meubles de la philosophie - Thomas Constantinesco (Transatlantica)
According to Stanley Cavell, America has “never ever expressed itself philosophically,” unless it be “in the metaphysical riot of its greatest literature.” What is this odd coupling, this strange union of literature and philosophy? What does it mean for philosophy to move in with literature? What does it mean to set up house in someone else’s home? With what furniture? Does philosophy have its own furniture? Is there a philosophy of furniture? These questions find a surprising echo, and maybe a few answers, in a short text by Edgar Allan Poe precisely entitled “The Philosophy of Furniture” (1840). Poe may not be a philosopher, but his texts surely are food for thought and his philosophy of furniture is an invitation to reflect on the materialist craze that drives nineteenth-century America, but also to think about what our furniture reveal of our relationship to ourselves and to others, and to consider the paradoxical link that unites philosophy and literature.